The gods of Greek hexameter poetry: from the archaic age to late antiquity and beyond - Clauss, James Joseph; Cuypers, Martine; Kahane, Ahuvia (Potsdamer altertumswissenschaftliche Beiträge, 2016)
Hiero's question : an introduction / James J. Clauss, Martine Cuypers and Ahuvia Kahane -- The justice of Zeus in the Theogony? / Jenny Strauss Clay -- The gods in the narratives of the Homeric Hymns / Andrew Faulkner -- Divine perspective and the plots of Zeus in the Hesiodic Catalogue / Kirk Ormand -- Herding cats : Zeus, the other gods, and the plot of the Iliad / Jim Marks -- Poseidon in the Odyssey / Richard P. Martin -- The gods in cyclic epic / Christos Tsagalis -- Ares in the Pseudo-Hesiodic Shield / Timothy Heckenlively -- Heldendämmerung anticipated : the gods in Apollonius' Argonautica / James J. Clauss -- Zeus in Aratus' Phaenomena / John Ryan -- Gods in Callimachus' Hymns / Ivana Petrovic -- Gods in fragments : Callimachus' Hecale / Massimo Giuseppetti -- Erotic battles? Love, power-politics and cosmic significance in Moschus' Europa and Eros on the run / A.D. Morrison --
Literaturverzeichnis: Seite 407-442
Keywords: Aufsatzsammlung; Götter; Hexameter; Versdichtung; Griechisch